The Quality of High-Performance Concretes as a Function of their Hardening Time - Kapelko, Aleksander (Engineering Transactions, 2015)
In the paper, the results of the author's investigations on the long-term variation of some technological properties of cement concrete are presented. The experiments were carried out using basalt aggregate, natural sand, Portland cement CEM I 42.5 R, acrylic superplasticizer and silica fume. By adding superplasticizer, the amount of water in the concrete mix was reduced by 19–22% whereby the water-binder ratio was reduced from 0.40 to 0.29–0.32. Ali the tested concretes meet the compressive strength requirements of the adopted classification of HPCs (compressive strength of at least 60 MPa after 28 days of hardening). Long-term testing has confirmed that compressive strength as a function of time is steadily increasing. The increase is rapid in the first days of hardening. Logarithmic curves are a good approximation of the relationship between compressive strength and hardening time. The investigations have demonstrated that superplasticizer and silica fume significantly reduce the water absorption of the concrete. Also increasing in time is the modulus of elasticity. The concrete modified with superplasticizer and silica fume seems to be more brittle than the reference concrete.